On an Algebra of Fuzzy m-ary Semihypergroups - Naco, Adrian; Peposhi, Anila; Hila, Kostaq; Onar, Serkan; Ersoy, Bayram ali (UNIV CRAIOVA, 2025)
In this paper we deals with the fuzzy m-ary semihypergroups, fuzzy hyperideals and homomorphism theorems on m-ary semihypergroups and fuzzy m-ary semihypergroups. We also, introduce and study some classes of fuzzy hyperideals that of pure fuzzy, weakly pure fuzzy hyperideals in m-ary semihypergroups and some properties of them are investigated. We identify those m-ary semihypergroups for which every fuzzy hyperideal is idempotent. We also characterize the m-ary semihypergroups for which every fuzzy hyperideal is weakly pure fuzzy.
Keywords: m-ary semihypergroup; pure (weakly pure) fuzzy hyperideal; regular (weakly regular) m-ary semihypergroups; Mathematics